2017
DOI: 10.1021/acs.inorgchem.6b02384
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of CO2 Catalyzed by Re(pyridine-oxazoline)(CO)3Cl Complexes

Abstract: A series of rhenium tricarbonyl complexes coordinated by asymmetric diimine ligands containing a pyridine moiety bound to an oxazoline ring were synthesized, structurally and electrochemically characterized, and screened for CO reduction ability. The reported complexes are of the type Re(N-N)(CO)Cl, with N-N = 2-(pyridin-2-yl)-4,5-dihydrooxazole (1), 5-methyl-2-(pyridin-2-yl)-4,5-dihydrooxazole (2), and 5-phenyl-2-(pyridin-2-yl)-4,5-dihydrooxazole (3). The electrocatalytic reduction of CO by these complexes wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 79 publications
(194 reference statements)
3
51
0
Order By: Relevance
“…Despite this, continuing research efforts to produce commercially viable functionalization of CO 2 remains some distance away . Currently, much of the literature regarding molecular electrochemical activation of CO 2 still continues to explore the catalytic properties of the heavier members of Group‐7 (Re), Group‐8 (Ru and Os) and Group‐9 (Rh, and Ir) triads. These “first‐generation” electrocatalysts must be phased out; encouragingly, cheaper alternatives exist within the same groups – Mn substituting Re, Fe substituting Ru and Os, and Co substituting Rh and Ir .…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, continuing research efforts to produce commercially viable functionalization of CO 2 remains some distance away . Currently, much of the literature regarding molecular electrochemical activation of CO 2 still continues to explore the catalytic properties of the heavier members of Group‐7 (Re), Group‐8 (Ru and Os) and Group‐9 (Rh, and Ir) triads. These “first‐generation” electrocatalysts must be phased out; encouragingly, cheaper alternatives exist within the same groups – Mn substituting Re, Fe substituting Ru and Os, and Co substituting Rh and Ir .…”
Section: Methodsmentioning
confidence: 99%
“…They demonstrated that the catalysts presented superior relative turnover frequencies to the Re(bpy)(CO) 3 Cl catalyst due to the presence of the oxazoline ligand, which is a better σ donor than pyridine. Also, they found out that the reaction of these complexes proceeded more quickly in acetonitrile than in DMF and dimethyl sulfoxide (DMSO) due to a protonation‐first mechanism [168] . Following modifications of the rhenium bpy‐based catalyst using benzylic pendant amines, the complex Re(dEAbpy)(CO) 3 Cl (dEAbpy=N,N′‐(([2,2′‐bipyridine]‐6,6′‐diylbis(2,1‐phenylene))bis(methylene))bis(N‐ethylethanamine)) was prepared, showing selective production of CO, with 11.8±3.5 % HCOOH formation.…”
Section: Electrochemical Co2 Reduction Reaction (Co2rr) Rhenium Bipyridine‐based Catalystsmentioning
confidence: 99%
“…In an example closely related to this study, complexes [Cp*Ir(bpy‐R,R′)Cl] + prepared with various unsymmetrically substituted bipyridine ligands were found to have a moderate electrocatalytic activity in CO 2 reduction but with no direct correlation between the redox potentials and the catalytic activity. Regarding the replacement of the bpy ligand by another redox non‐innocent ligand, rationalization is still missing: none of the [Re(N ^ N)(CO) 3 X] complexes with N ^ N being 2‐pyridyl‐1,2,3‐triazole ligand was found to outperform the benchmark catalyst [Re(bpy)(CO) 3 X], whereas a Re‐pyridyl‐NHC species displays a slightly higher faradic efficiency and some Re‐pyridine‐oxazolines higher TOF but decreased faradic efficiency; [Mn(N ^ N)(CO) 3 X] where N ^ N stands for iminopyridines or α‐diimines do catalyze the conversion of CO 2 to CO and CO 3 2– but at the cost of an increased overpotential. These examples underline that more structure‐activity relationships studies are needed to improve our understanding of the relevant parameters and to find a good balance between decreasing the overpotential and keeping sufficient reducing power in the redox non‐innocent ligand .…”
Section: Resultsmentioning
confidence: 99%